EFFICIENTLY OVERSEEING AND MONITORING DATA WITHIN THE PHARMACEUTICAL SUPPLY CHAIN (International Journal of Food and Nutritional Sciences, 2022)
The authors conduct research into pharmaceutical inventory management and data handling practices. Fake pharmaceuticals pose a serious threat to the well-being of patients when this occurs. The authors advocate for the use of radio frequency identification (RFID) and related technologies, such as EPC Global's EPCIS and IBM's RFID Information Center, to monitor the movement of mass-produced, uniquely marked commodities across the supply chain. This situation is analyzed with the help of Transaction Cost Theory and the Theory of Collective Action. Everyone involved in the distribution of pharmaceuticals must act lawfully and cooperate without interruption